Does Credit Influence Fertilizer Intensification in Rice Farming? Empirical Evidence from Côte D’Ivoire - N’Banan Ouattara; Xueping Xiong; Lacina Traoré; Calum G. Turvey; Ruiting Sun; Abdelrahman Ali; Zié Ballo (Agronomy, 2020)
In Côte d’Ivoire, the use of fertilizers in rice farming still remains low. Credit constraints have been frequently reported as the main reason hampering rice farmers from reversing this situation. However, there is no empirical evidence on the link between rice farmers’ access to credit (AC) and fertilizer intensification (FI). This article examines this issue by using a sample of 600 rice farmers randomly selected in seven rice areas. Data are analyzed by the IV-Probit and IV-Tobit models. The results reveal that FI and AC reciprocally influence each other, implying that they are endogenous. An increase of credit by XOF 100 could increase the quantity of fertilizer used by 2.70 kg, all other things being equal. Moreover, FI and AC are strongly influenced by some socio-economic, rice farm, and institutional factors. Policymakers should take actions to facilitate rice farmers’ access to credit and subsidized fertilizers. Other relevant explanatory variables should be considered in rice farming development policies. By providing empirical evidence of the link between rice farmers’ access to credit and fertilizer intensification in Côte d’Ivoire, this paper contributes to the agricultural finance literature.